From biosafety to infection control in dentistry - Mónica Rodríguez Uramis; Yunier Arpajón Peña; Ana Ludys Sosa Pérez (Editorial Ciencias Médicas, 2014)
During the performance of dental procedures, both patients and staff are under permanent risk of contact with biological agents from saliva, blood and respiratory secretions. Hence the importance of complying with biosafety standards in laboratories and during the performance of waste disposal tasks. Moreover, alongside the recommendations contained in biosafety manuals, attention should also be paid to those included in infection prevention and control programs. The objective of this work is to relate biosafety standards and principles to the principles contained in infection prevention and control programs for dentistry, and identify the aspects to be borne in mind when developing such programs. A bibliographic review was conducted in the main medical databases (Scielo, Pubmed, EBSCO, Hinari) of scientific papers and programs from various countries related to infection prevention and control in dentistry. The Biosafety Manual contained in Annex 28 of the National Comprehensive Dental Care Program was also consulted. Data were collected about similarities and differences between biosafety principles and the principles contained in infection prevention and control programs for dentistry. Additionally, information was obtained about the aspects to bear in mind when designing such programs. Biosafety standards should be considered when developing and implementing an infection prevention and control program for dental services.